The correlation between visual electrophysiology test with retinal nerve fibre layer thickness and advance glaucoma interventional study score in primary angle closure glaucoma patient. - Akhtar Ali, Ahmad Nurfahmi (2014)

(untitled)
INTRODUCTION Primary angle closure glaucoma (PACG) causes more blindness in Asian population. Diagnosis and monitoring remains a challenge especially due to structural-functional discrepancy in evaluating optic nerve head (ONH) in PACG. Visual electrophysiology (pattern electroretinogram (PERG) and pattern visual evoked potential (PVEP)) has the capability in detecting functional impairment of retina ganglion cells (RGC). It has the potential as complimentary test to the existing standard structural and functional test for ONH evaluation in glaucoma in general and PACG specifically. OBJECTIVE To evaluate visual electrophysiology response and retina nerve fibers layer (RNFL) thickness in PACG. The correlation between visual electrophysiology with the glaucoma severity based on RNFL thickness and Advance Glaucoma Interventional Study (AGIS) score were also evaluated. MATERIALS AND METHODS A comparative cross sectional study was conducted in Hospital University Sains Malaysia involving 66 samples of PACG patients and controls. A Complete ocular assessment was done to confirm the diagnosis of PACG. Evaluation of structural changes of RNFL of ONH was conducted using Cirrus SD-OCT (Carl Zeiss Meditec Inc, USA) with good signal strength ( ≥ 6/10).AGIS score was performed on a reliable reproducible visual field of two consecutive Humphrey’s visual field (24-2) analysis. PERG (0.8º checks size) and PVEP(0.25º checks size) was conducted by a trained technician. Independent t-test, ANCOVA and Pearson’s correlation coefficient analysis were used in analysis. RESULTS There was statistically significant reduction in amplitude and latency in of PERG in PACG patients (p<0.001). There was also significant reduction in magnitude of amplitude (p<0.001) and shorten of P100 latency in PVEP (p<0.001). PACG patients had significant smaller disc area (2.03±0.26) compared to controls (2.27±0.35). There was also significant thinner RNFL analysis in all quadrant of the ONH in PACG patients (p<0.001). RNFL thickness shown a significant strong positive correlation with the PERG amplitude of N95 (r = 0.54, p = 0.001). AGIS score showed a significant negative correlation between N35 (r = - 0.36, p = 0.041) and N95 (r = - 0.49, p = 0.003) of PERG. Similarly the positive and negative correlations were seen between RNFL thickness and AGIS score respectively with PVEP. However it was not statistically significant. CONCLUSION Visual electrophysiology showed significant changes in PACG patients. There was significant correlation between PERG and existing standard structural and functional analysis of ONH. PERG is the potential alternative tools for evaluation of functional changes of ONH in PACG patients. KEY WORDS ‘Primary angle closure glaucoma (PACG)’, pattern electroretinogram (PERG), pattern visual evoked potential (PVEP), retina nerve fiber layer (RNFL), Advance Glaucoma International Study (AGIS).